2020
DOI: 10.1111/ijn.12880
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the ‘Self‐Management and Transition to Adulthood with Rx = Treatment Questionnaire’ in Chinese children and young people with chronic diseases

Abstract: Aims The aims of this work were to translate, culturally adapt and evaluate the reliability and validity of the Chinese version of the Self‐Management and Transition to Adulthood with Rx = Treatment Questionnaire. Background Children and young people with chronic diseases are expected to start self‐managing their diseases and have a smooth and coordinated transition from paediatric‐ to adult‐oriented care. Design This study involved the cultural adaptation of a questionnaire into Chinese and examined its facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Ten studies focused on multiple chronic conditions such as kidney disease, systemic lupus erythematosus, inflammatory bowel disease, hypertension, renal transplant, and systemic lupus erythematosus ( 2 , 29 , 53 61 ). Four studies did not specify the chronic condition of their sample ( 57 , 62 – 64 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies focused on multiple chronic conditions such as kidney disease, systemic lupus erythematosus, inflammatory bowel disease, hypertension, renal transplant, and systemic lupus erythematosus ( 2 , 29 , 53 61 ). Four studies did not specify the chronic condition of their sample ( 57 , 62 – 64 ).…”
Section: Resultsmentioning
confidence: 99%
“… † The same scale is used by Karahroudy et al ( 48 ) (Author of included study); ‡The Chinese version is C-SMODA by Guo et al ( 47 ) (included study); §The Malay version is by Tan et al ( 51 ) (included studies); ¶ Translated in English; The same scale is also used by Sawicki et al ( 60 ) (included study); *The German version is TRAQ G.V 15 by Culen et al ( 55 ); # The same scale is also used by Shackleford et al ( 40 ) and Zhong et al ( 61 ) (included studies); °The same scale is used by Cohen et al ( 54 ) ◆ The Spanish version is C TRxANSITION Scale™ Version 3 by Cantú-Quintanilla et al ( 53 ) (included study); ◼ The Chinese version is by Sheng et al ( 2 ) and Ma et al ( 57 ) (included studies). …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The exploratory factor analysis using principal component analysis with varimax rotation and confirmatory factor analysis employing structural equation modelling procedures indicated that the STARx Questionnaire had four dimensions in Chinese culture with 18 items using a 5‐point Likert format as per the original measure (Ma, 2020). The scale‐level content validity average scores (S‐CVI/Ave) of the expert content validity scores of the Chinese version of STARx Questionnaire was 0.96 and four factors were identified as Medication Management (Items 2, 5, 6, 8, 12 & 16), Health‐Care Engagement (Items 1, 3, 4, 7 & 9), Provider Communication (Items 13, 14, 15, 17 & 18) and Disease Knowledge (Items 10 & 11; Ma et al, 2020). Higher scores indicate better transition readiness.…”
Section: The Studymentioning
confidence: 99%
“…Higher scores indicate better transition readiness. The overall Cronbach's α of the Chinese version of the STARx Questionnaire was 0.81 and the subscales were over 0.75 (Ma et al, 2020).…”
Section: The Studymentioning
confidence: 99%